Determinants Of Caregivers’ Vaccination Intention With Respect To Child Age Group - Alqahtani, Muhannad Ali; Tumaiyhi, Khaled Hassan; mashni, ‏Fawaz ahmad mohamad; Othaybi, Majed Ibrahim; Alqasir, Nasser Ibrahim Makki; HAJAJI, NAWAF AHMED; Althurwi, Hussain Mohammed Hussain; Ahmed Alhassan Alqabi; Yahya Mohammed Yousef Tumaiyhi; Khalid Mohammed Alfadhli (Migration Letters, 2023)
Objective: This study examined how knowledge, risk perception, health beliefs and multidimensional health locus of control (HLC) were associated with caregivers’ intention to vaccinate their child, and how the associations varied across child age groups. Setting: Makkah, Saudi Arabia. Methods: The cross-sectional survey was conducted via a face-to-face interview among 1017 nationally representative caregivers who had children aged 12 or younger. The outcome variable was caregivers’ intention to vaccinate their children. Results: Hierarchical regression analysis indicated that risk perception was negatively associated with vaccination intention only among the age group 4–6 (β=−0.127, p<0.05). Perceived benefit was the only significant predictor of the outcome variables for all three age groups. In contrast, perceived barrier was negatively related to vaccination intention only among the age group 7–12 (β=−0.104, p<0.05). Internal HLC was positively related to vaccination intention only among the age group 7–12 (β=0.151, p<0.001), while chance HLC was negatively related to vaccination intention only among the age group 0–3 (β=−0.121, p<0.05). Conclusions: This study identifies key vaccination intention determinants that are differentially associated with caregivers’ children’s age groups. To improve vaccination rates, it suggests the need for strategies tailored to children’s age.